1997
DOI: 10.1002/(sici)1099-1018(199701)21:1<17::aid-fam590>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Mattress Composites in the Cone Calorimeter

Abstract: An investigation of cone calorimeter test procedures was performed using two types of mattress composites with various specimen preparations and equipment configurations. The objective was to discover suitable procedures for testing mattress composites. Concurrent with this work a much larger and more sophisticated project known as CBUF 1 was underway in Europe. One of CBUF's secondary objectives was to provide an appropriate test protocol for testing upholstered furniture composites, including mattresses. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The 35 kW/m 2 level is often associated with a mild fire exposure, and the 50 kW/m 2 level is likewise associated with a well‐developed fire. In other studies in which the cone calorimeter was used to evaluate specimens of fabric/foam mattress composites, a heat flux level of 35 kW/m 2 is typically used . The 35 kW/m 2 level is also the flux level specified in ASTM E 1474, standard test method for determining the heat release rate of upholstered furniture and mattress components or composites using a bench‐scale oxygen consumption calorimeter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 35 kW/m 2 level is often associated with a mild fire exposure, and the 50 kW/m 2 level is likewise associated with a well‐developed fire. In other studies in which the cone calorimeter was used to evaluate specimens of fabric/foam mattress composites, a heat flux level of 35 kW/m 2 is typically used . The 35 kW/m 2 level is also the flux level specified in ASTM E 1474, standard test method for determining the heat release rate of upholstered furniture and mattress components or composites using a bench‐scale oxygen consumption calorimeter.…”
Section: Resultsmentioning
confidence: 99%
“…The residual mass fraction was the highest for the SRRC‐2 treatment at each of the heat flux levels. In ASTM E 1474 and in studies reported in the literature , the specimen tested in the cone calorimeter is a fabric/foam composite, which is intended to represent the use of the fabric with a mattress. Various specimen configurations of the fabric/foam composites were investigated by Fritz and Hunsberger .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (Horrocks et al 2001) have also shown that PHRR values might be dependent upon the fabric surface and fabric construction of the tickings in addition to their fiber content and fabric finish. Study (Fritz & Hunsberger 1997) on the flammability testing of mattress composites have shown that the quilting also affects burning behavior, such that quilted specimens exhibit slightly higher THR values as compared to non-quilted specimens when tested under the cone calorimeter. One of the probable reasons for this kind of fire performance may be attributed to the fact that flame spread in quilted specimens is much slower.…”
Section: Tickingmentioning
confidence: 99%
“…While quilting imparts more cushioning and insulation by creating large air pockets within the quilted structure, the quilting pattern itself also impacts the burning behavior. When tested under the cone calorimeter, composite specimens with quilted tickings exhibit slightly higher total heat release rates (THR) values as compared to non-quilted ticking specimens (Fritz & Hunsberger 1997). One of the probable reasons for this kind of fire performance is that flame spread in quilted specimens is slower.…”
Section: Contributions To Flammability: Tickingsmentioning
confidence: 99%